Room Allotment Management to Increase Room Occupancy and its Implication to Hotel Management Strategy - Rama, Vanny Oktafia Putri; Astawa, I Ketut; Wendri, I Gusti Made; Mudana, I Gede (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
In the tourism industry, fluctuations in room occupancy are common. Many hotels offer various types of accommodation and service options needed by guests, causing competition between one hotel and another hotel. The purpose of this study is to find out how the management of room allotment in an effort to increase room occupancy at a one 5-star hotel in the southern part of Bali. This study was conducted using a qualitative descriptive method with analysis of POAC (Planning, Organizing, Actuating, Controlling) and SWBR (Strength, Weakness, Benefit, Risk). Data is obtained using the interview method. This study also explains how the implications of room allotment management on management strategy at the hotel. The results of this study indicate that the management of the allotment room has been done quite well but has not provided maximum results in increasing room occupancy. The implications of giving room allotment based on management functions indicate that negotiations still have problems with the prices determined, there are strengths, weaknesses, benefits and risks in organizing the people who regulate the room allotment, the room allotment given has not been 100% fulfilled and there is no a special system to control room allotment. Future research is recommended with regard to the effectiveness of room allotment through the system.